The standards-based integrated library a collaborative approach for aligning the library program with the classroom curriculum - Miller, Donna P. 1948-; Gale Group (Worthington, Ohio Linworth Pub., 2004)
A handbook that describes a specific collaborative process for library media specialist and classroom teacher to use in planning teaching units. Written for K-12 educators. Also provides suggested book lists, web sites, and professional resources.
Components of the program, the "what" -- Rationale for the program, the "why" -- The planning team, the "who" and "how" -- Implementing the program, the "how-to's" -- Implementing the program, grades K through two -- Implementing the program, grades three through six -- Implementing the program, secondary grades -- Challenges to overcome, the "what if's" -- Benefits of the program, the "warm fuzzies".
Electronic reproduction.
Keywords: School libraries -- Activity programs -- United States; Library orientation for school children -- United States; Information literacy -- Study and teaching (Elementary) -- Activity programs -- United States; School librarian participation in curriculum planning -- United States; Media programs (Education) -- United States; Active learning -- United States; Electronic books